Implementation of Green Open Space Policy in Cirebon City as Part of Efforts to Achieve Sustainable Cities and Communities - Gita Aditya Purwandani; N Nursahidin (Athena: Journal of Social, Culture and Society, 2026)
Green Open Spaces (GOS) are the physical embodiment of sustainable cities and communities that align with the Sustainable Development Goals (SDGs), specifically the goal of Sustainable Cities and Communities. The provision of green open spaces is regulated under Law No. 26 of 2007 on Spatial Planning, which stipulates that cities and regencies must have at least 30% green open space relative to the total area of the city or regency. The city of Cirebon has only 9.4% green open space within its 39.48 km² area, this figure is still far below the established minimum requirement. Therefore, this study is grounded in Edward III’s theory of policy implementation, using a descriptive qualitative method with interview and direct observation techniques. The results of the study indicate that the implementation of green open spaces in Cirebon City has not been optimally achieved due to land constraints, the large amount of land that has been converted for other uses, and budget limitations. Consequently, the implementation of green open space policies in Cirebon City has not been optimally achieved and is not yet aligned with the SDGs.